2015
DOI: 10.5588/pha.14.0066
|View full text |Cite
|
Sign up to set email alerts
|

Patient delay in the diagnosis and treatment of tuberculosis in China: findings of case detection projects

Abstract: Patient delay in accessing health care in China was lengthy; TB care and control needs to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 16 publications
8
27
2
Order By: Relevance
“…Of the 278 DM patients with a positive TB symptom screen, those with two or more symptoms accounted for 18% of cases but had a much higher risk of not attending the TCC. Although this has been found previously , this finding does conflict with traditional assumptions that patients with more TB symptoms proceed to healthcare provision more quickly than those with fewer symptoms. Previous reports have demonstrated that TB patients with more TB‐specific symptoms, particular haemoptysis, are less at risk of delay in accessing diagnostic and care facilities .…”
Section: Discussioncontrasting
confidence: 87%
“…Of the 278 DM patients with a positive TB symptom screen, those with two or more symptoms accounted for 18% of cases but had a much higher risk of not attending the TCC. Although this has been found previously , this finding does conflict with traditional assumptions that patients with more TB symptoms proceed to healthcare provision more quickly than those with fewer symptoms. Previous reports have demonstrated that TB patients with more TB‐specific symptoms, particular haemoptysis, are less at risk of delay in accessing diagnostic and care facilities .…”
Section: Discussioncontrasting
confidence: 87%
“…Delay in accessing health services has been reported to be significantly associated with increased age, and has been highlighted in other research. 6 The longer patient delays associated with treatment failure and death should be addressed as a priority by the national and sub-national TB programmes by enhancing patient support and community service. The association of short patient delays (0-30 days) with LTFU needs to be further investigated, as this was highlighted as a risk factor in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the design, setting, sites, patients, interventions, data collection and ethics review of the FIDELIS projects have been published elsewhere. 6 Of the 15 FI-DELIS projects in China, we report here the findings from three projects, the Anhui (middle east), Guizhou (south west) and Shaanxi (north west) projects, which were implemented from 2004 to 2008.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak incidence of TB is mainly caused by new disease spread and increased incidence of latent infections; therefore, studies of the peak seasonal incidence peak should take into account the delay in diagnosis [27]. A previous study showed that the median TB patient delay is 93 days (range 68-128 days) [28]. Missed the early diagnosis and variable incubation periods of TB, will not only lead to a longer infectious period and increased transmission rates, but will also limit the reliability of the TB surveillance system and the effects of an early warning system [19,29].…”
Section: Discussionmentioning
confidence: 99%